Characterisation of HIV-1 transmission clusters and drug-resistant mutations in Denmark, 2004 to 2016 - Petersen, Andreas (Euro Surveill, 2018)
This study describes the prevalence of human immunodeficiency virus (HIV) drug resistance mutations among 1,815 patients in Denmark from 2004 to 2016 and characterises transmission clusters. POL sequences were analysed for subtype, drug resistance mutations and phylogenetic relationship. The prevalence of surveillance drug resistance mutations (SDRM) was 6.7%, while the prevalence of drug resistance mutations (DRM) with a clinical impact was 12.3%. We identified 197 transmission clusters with 706 patients. Patients 40 years or older were less likely to be members of a transmission cluster and patients in transmission clusters were less likely to be infected abroad. The proportion of late presenters (LP) was lower in active compared with inactive clusters. Large active clusters consisted of more men who have sex with men (MSM), had members more frequently infected in Denmark and contained a significantly lower proportion of LP and significantly fewer patients with DRM than small active clusters. Subtyping demonstrated that the Danish HIV epidemic is gradually becoming more composed of non-B subtypes/circulating recombinant forms. This study shows that active HIV-1 transmission has become increasingly MSM-dominated and that the recent increase in SDRM and DRM prevalence is not associated with more sustained transmission within identified transmission networks or clusters.